A Jali (lattice) Window - Temples of India Project Team (Jio Institute, 2024)
The western side of the southern garbhagriha (sanctum sanctorum) of the Mahakal Temple features a bhadra (central offset) adorned with a jali (lattice) window. The rectangular frame of this window is embellished with a motif resembling a four-petaled flower.